Developing an agenda for the history of women religious in Ireland: historiography and potentiality. Issue 170 (November 2022) - Raftery, Deirdre
Abstract: In 'An Agenda for women's history in Ireland, 1500–1900' (1992), Margaret MacCurtain, Mary O'Dowd and Maria Luddy noted that research on convents and women religious (nuns/sisters) in Ireland was beginning to open up in the 1980s. They also suggested areas that merited the attention of scholars, including the experience of vowed religious life by women, issues of class and power within Irish convents, and the role of nuns in Irish society. This article examines historiographical developments, with a view to seeing whether or not scholars rose to the challenges posed in 1992. Additionally, it considers areas that still demand attention.